2012
DOI: 10.1002/hed.21493
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular cuniculatum carcinoma: Apropos of 3 cases and literature review

Abstract: The diagnosis is often delayed. Although cuniculatum carcinoma displays aggressive behavior locally, lymph node infiltration and metastasis are rare. The therapy of choice is surgical removal with free margins, after which the prognosis is excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 4 publications
(19 reference statements)
4
44
1
3
Order By: Relevance
“…Similarly, other studies have also reported the use of multiple antibiotics to treat a misdiagnosed abscess or osteomyelitis [12,14,16,24]. In regards to esophageal carcinoma cuniculatum, a number of authors have also reported carcinoma cuniculatum mimicking benign esophageal lesions such as Crohn's, esophagitis, and esophageal strictures [13].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, other studies have also reported the use of multiple antibiotics to treat a misdiagnosed abscess or osteomyelitis [12,14,16,24]. In regards to esophageal carcinoma cuniculatum, a number of authors have also reported carcinoma cuniculatum mimicking benign esophageal lesions such as Crohn's, esophagitis, and esophageal strictures [13].…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, an increasing number of reports describe CC involving head and neck sites, predominantly the oral cavity [2,4,[9][10][11][13][14][15][16][17][18][19][20][21][22]. Table 1 summarizes all reports of CC occurring in the head and neck which could be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic dilation of these channels is not uncommon. Like verrucous carcinoma (VC), CC tends to be well differentiated with low grade cytonuclear features, making diagnosis difficult to establish on small biopsy samples, often leading to delays in treatment [2]. Although similarities exist between CC and VC, and the literature occasionally uses the terms interchangeably, there are some differences, and the 2005 edition of the WHO Pathology and Genetics of Head and Neck Tumours includes CC as a separate variant of squamous cell carcinoma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Verrucous carcinoma is now known to arise in a variety of epithelial sites, most often the oral mucosa, the larynx, the skin of the genitalia, and the skin of the plantar aspect of the foot [4][5][6][7]. Cervical and distant metastases have not been reported in cases of classic verrucous carcinoma [8,9].…”
Section: Introductionmentioning
confidence: 99%